Variety comparison and modelling flowering of Limonium perezii (Stapf) Hubb. x Limonium sinuatum (L.) Mill. 'LSLP4' : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Horticultural Science, Massey University, Palmerston North, New Zealand - Chen, Jianyu (Massey University, 2005)
A series of new inter-specific hybrids have been derived between L. perezii and L. sinuatum. One of the selections 'LSLP4' offers potential as a cut flower. Precise knowledge on quality, yield and timing of these selections, as well as scheduling 'LSLP4' accurately in commercial production were required. To address these needs, this project comprised both a variety trial and an experiment to model the time to flower. Plants of 'LSLP4', 'LSLP5' (a sibling of 'LSLP4'), L. perezii and L. sinuatum derived from tissue culture were grown in a temperature-controlled (daily mean temperature around 20°C) greenhouse and long-day photoperiod. With the exception of the inferior wing characteristic, the yield, timing, and quality as well as the consistency of yield and quality of 'LSLP4' were intermediate or superior to L. sinuatum and L. perezii. The potential of 'LSLP5' as a cut flower could not be assessed due to its failure to flower during the variety trial. To develop a predictive model for time to flower of 'LSLP4', 7 sequential plantings were conducted from autumn through to late spring, utilizing one of two light regimes (50% shaded and no-shade). This resulted in 11 treatments of average daily light integral (DLI). Duration from transplanting to first visible flower bud (DTV) was correlated with average DLI, with the response being saturated above 15 mol.m-2.d-1. This relationship between DTV and average DLI is the foundation of a pre-planting predictive model for 'LSLP4'. DTV was also correlated with leaf number accumulation rate (LNAR) and ground cover index increase rate (GCIR). The combination of average DLI and LNAR together as predictors of DTV improved the r² of the model over that using DLI alone from 88% to 92%, which subsequently formed the basis of a 'post-planting' predictive model. It was recommended that growers of 'LSLP4' for cut flowers use the 'pre-planting' model to schedule planting dates and predict flowering time according to historical DLI data. Once planting occurs, and actual DLI and LNAR are collected, the prediction of DTV can be refined by the post-planting model.
Keywords: Limonium Varieties; Flowering Limonium